Elimination des polluants par des carbones activés dopés - BAASSOU ZOHRA (My University, 2024)
Hexavalent chromium (Cr(VI)) is a water-soluble and highly toxic form of chromium compound recognized as a carcinogen and can cause various health problems. Synthetic dyes are both toxic and responsible for coloring wastewater, are not biodegradable, and once discharged, cause alterations to the aquatic environment. This research studies the use of activated carbon (AC) derived from Ficus carica leaves for the removal of Cr(VI) and AB-40 from water. The effect of impregnation rate on the characterization and performance of activated carbons (AC-30, AC-60, 157 AC-100, AC-150, and AC-200) for removing Cr(VI) and AB-40 was investigated. The physicochemical and textural properties of the produced activated carbons (ACs) were characterized using various analyses, including XRD, SEM-EDX, TGA, FTIR, iodine index, methylene blue index, point of zero charge (pHPZC), and Boehm titration. It was found that the prepared ACs (AC-30, AC-60, and AC-100) are primarily microporous with some mesoporosity for AC-100, which has a specific surface area of 683.75 m²/g and a pore volume of 0.468 cm³/g. Additionally, AC-200 is mainly mesoporous with a specific surface area of 423.22 m²/g and a pore volume of 0.705 cm³/g. It was determined that high impregnation favors the formation of mesopores and leads to a relatively high specific surface area. Surface chemistry characterization of the ACs prepared at 600°C showed slight acidity confirmed by the pHPZC values, attributed to the acidic functional groups content, mainly composed of lactonic and phenolic groups. It was noted that as the impregnation rate increases from 30% to 200%, the oxygen content increases from 20.8% for AC-30 to 47.1% for AC-200, confirmed by the obtained pH values. These results highlight the slightly acidic nature of the prepared activated carbons. It was found that AC-100 impregnated at a (H₃PO₄/biomass) ratio of 100% shows very effective removal of Cr(VI), while AC-200 impregnated at a (H₃PO₄/biomass) ratio of 200% shows very effective removal of AB-40. The prepared ACs were modified with ethylenediamine (EDA) to enhance their performance. The results show that the adsorption capacity of the modified ACs showed a significant improvement compared to the unmodified ACs. The maximum adsorption capacities for the removal of Cr(VI) for AC-100 and its modified form are 155.22 and 203.25.mg/g, respectively, as determined by the Langmuir isotherm. On the other hand, the maximum adsorption capacities for the removal of AB-40 for AC-200 and its modified form are 357.14 and 625 mg/g, respectively, also as determined by the Langmuir isotherm. The results of this study confirm that EDA can be used to enhance the efficiency of activated carbon (AC) derived from Ficus carica leaves for removing Cr(VI) and AB-40 from water. Furthermore, SEM images and FTIR spectral analysis successfully confirmed surface modifications, especially peaks that provided conclusive evidence of the chemical modification of ACs prepared with EDA. Isotherm studies showed that the adsorption of Cr(VI) and AB-40 is monolayer on homogeneous surfaces of ACs and AC-EDAs. 158 Keywords: Modified activated carbon; Chemical activation; Ficus Carica leaves; Adsorption; Pollutants (Cr(VI) and AB-40); Ethylenediamine
Keywords: Modified activated carbon; Chemical activation; Ficus Carica leaves; Adsorption; Pollutants (Cr(VI) and AB-40); Ethylenediamine